Unravel subseafloor hydrothermal leaching and magmatic degassing during chimney formation at Kolumbo volcano - Simon Hector; Qasid Ahmad; Clifford G.C. Patten; Massimo Chiaradia; Paraskevi Nomikou; Stephanos Kilias; Alexandre Peillod; Simon Wagner; Jochen Kolb (Scientific Reports)
Abstract Hydrothermal chimneys are the upmost expression of fluids, metals and ligands transfer from the subseafloor to the hydrosphere, eventually forming seafloor massive sulfides. In volcanic arc settings, both magmatic and hydrothermal fluids occur together. While each fluid reflects different metal mobilizing mechanisms (i.e. magmatic degassing and hydrothermal leaching of subseafloor lithologies), it is unclear which metals they respectively provide to the budget of the chimneys. We investigate the metal sources and mobilizing mechanisms associated with a gold-rich hydrothermal field from Kolumbo volcano (South Aegean Volcanic Arc, Greece) by comparing Pb isotope ratios of ore minerals from a chimney with those of potential source rocks. Four key findings result from our study: (1) Kolumbo volcanic rocks are the main source of Pb for the chimneys; (2) Magmatic assimilation of Cycladic Basement allows to track magmatic differentiation and identify metal mobilizing mechanisms for Pb and metals with similar behavior. At Kolumbo, magmatic degassing mobilizes As, Ag, Au, Cu, Hg, Sb, Sn and Zn along with Pb, while hydrothermal leaching of rhyolite provides Tl and likely some base metals to the chimneys; (3) Magmatic fluids contributed to galena and Sb-Pb sulfosalts formation while pyrite formed from hydrothermal fluids leaching rhyolite; (4) Galena growth zones in pyrite reveal episodic pulses of magmatic fluids during the chimney growth. The combined use of Pb isotopes on ore minerals and source rocks provides an additional tool to discriminate between magmatic and hydrothermal fluids contribution during seafloor massive sulfide formation, especially in arc settings where magmatic assimilation of crustal material with distinct isotopic signature is more likely to occur.